Habitat features of urban forest fragments supporting native lizards in the presence of introduced mammals : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Conservation Biology at Massey University, Albany, New Zealand - Nichols, Kelsey Rhonda Naina (Massey University, 2014)
Introduced species are responsible for declines and extinctions of native biota around the world, particularly on islands where native species are often more vulnerable to the effects of invaders due to a lack of shared evolutionary history. New Zealand’s native lizards have suffered considerable range contractions, declines and extirpations as a result of predation and competition from introduced mammals, with some species being more vulnerable than others. Little is known about the mechanisms which allow some grounddwelling native lizards to persist in the presence of introduced mammals. In this study, I describe the species composition and abundance of ground-dwelling lizard and introduced mammal assemblages in urban forest fragments, and investigate the relationship between them. I also describe the habitats used by native ground-dwelling lizards where introduced mammals are also present and investigate habitat features that may be important in promoting the coexistence of native lizards with introduced mammals. Finally, I compare various methods for surveying lizard (hand searching, artificial cover objects, pitfall traps) and mammal (tracking tunnels, snap traps) populations in urban forest fragments. Estimating the proportion of tail loss can be used as a proxy to determine predation pressure on lizard populations. The rate of tail loss among urban lizards in this study was relatively high (41%), suggesting that these lizard populations are under considerable predation pressure. However, no relationship between the abundance of introduced mammals and native lizards was identified. Key features of the habitats supporting the highest abundance of native lizards in the presence introduced mammals include high canopy cover and high cover and structure of debris (leaf litter and branches/logs) in the lower shrub layer. Food availability in the form of invertebrate abundance does not appear to play a significant role in the coexistence of introduced mammals and native lizards, and the abundance of introduced mammals and exotic lizard competitors was not correlated with invertebrate abundance. Hand searching is the most efficient method for identifying lizards in urban bush fragments. ACOs and pitfall traps had only low efficiency in this study and are not recommended for future studies. I found that tracking tunnels may be an alternative to snap traps for indexing mammal abundance in urban environments where the risk of trapping non-target wildlife, pets and the public is high
Keywords: Lizards, New Zealand; Predation, New Zealand; Lizard habitats, New Zealand; Urban forest fragments; Introduced mammals, New Zealand; Predatory mammals, New Zealand